2016
DOI: 10.1037/xlm0000213
|View full text |Cite
|
Sign up to set email alerts
|

When enough is not enough: Information overload and metacognitive decisions to stop studying information.

Abstract: People are often exposed to more information than they can actually remember. Despite this frequent form of information overload, little is known about how much information people choose to remember. Using a novel “stop” paradigm, the current research examined whether and how people choose to stop receiving new—possibly overwhelming—information with the intent to maximize memory performance. Participants were presented with a long list of items and were rewarded for the number of correctly remembered words in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 53 publications
4
37
0
1
Order By: Relevance
“…Studies have shown that provision of superfluous information reduces one’s learning ability, leading to students forgetting key basics required for clinical examinations. 30 Further, where sessions led by senior clinicians are less exam orientated and cover content rarely examined in OSCE assessments, this study demonstrates that this novel NPT model offers a better representation of content encountered during summative examinations. 31…”
Section: Discussionmentioning
confidence: 79%
“…Studies have shown that provision of superfluous information reduces one’s learning ability, leading to students forgetting key basics required for clinical examinations. 30 Further, where sessions led by senior clinicians are less exam orientated and cover content rarely examined in OSCE assessments, this study demonstrates that this novel NPT model offers a better representation of content encountered during summative examinations. 31…”
Section: Discussionmentioning
confidence: 79%
“…Even in real learning contexts, however, students may sometimes stop learning because they, often falsely, believe that they have mastered the materials, even if they actually have not (e.g., students may feel that they understand perfectly how to solve quadratic equations when they are presented with the formula but they actually do not understand the logic behind it). In fact, literature in metacognition has repeatedly shown that learners are inaccurate and optimistic about their mastery of learning materials (e.g., learning foreign words), often terminating their learning behavior prematurely (e.g., Kornell and Bjork 2008;Murayama et al 2016).…”
Section: Moderators Of Information-seeking Behaviormentioning
confidence: 99%
“…That is, we need to make a choice on the information we want to acquire. In the context of school learning, we are often required to regulate our learning by selecting learning materials out of our own choice and deciding the amount of time to work on specific learning materials (Murayama, Blake, et al, 2016).…”
Section: Role Of Choice In the Development Of Situational Interestmentioning
confidence: 99%